2023
DOI: 10.1039/d3sm00182b
|View full text |Cite
|
Sign up to set email alerts
|

Probing the tightly bound layer in poly(vinyl alcohol) thin films using swelling measurements

Abstract: A strongly adsorbed, tightly bound polymer layer can exist at the polymer/substrate interface in polymer thin films and polymer nanocomposites. The characteristics of the tightly bound layer have long been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…As the thin film samples were verified to be optically transparent (extinction coefficient, k ≈ 0), the λ dependence of the refractive index can be modeled using the Cauchy dispersion equation given by, n false( λ false) = A + B λ 2 + C λ 4 where the A , B , and C are fit parameters. The C in eq has often been set to 0 without significantly affecting the quality of the fits. ,,, In the current work, we have verified that the inclusion of the term corresponding to C reduced the RMSE by less than 0.5%. In addition, the values of B and C were highly correlated which suggested that one of the two might be redundant.…”
Section: Methodssupporting
confidence: 58%
See 3 more Smart Citations
“…As the thin film samples were verified to be optically transparent (extinction coefficient, k ≈ 0), the λ dependence of the refractive index can be modeled using the Cauchy dispersion equation given by, n false( λ false) = A + B λ 2 + C λ 4 where the A , B , and C are fit parameters. The C in eq has often been set to 0 without significantly affecting the quality of the fits. ,,, In the current work, we have verified that the inclusion of the term corresponding to C reduced the RMSE by less than 0.5%. In addition, the values of B and C were highly correlated which suggested that one of the two might be redundant.…”
Section: Methodssupporting
confidence: 58%
“…After thoroughly rinsing with DI water and flushing with dry nitrogen gas, the substrates retained a SiO 2 layer of thickness of approximately 2 nm. Past literature has reported the presence of an oxide layer of similar thickness after such a treatment. ,,, Thin films of chitosan of varying thicknesses were produced by spin coating for 60 s at maximum speeds ranging from 3000 to 9000 rpm achieved using rotational accelerations of either 60 or 100 rpm/s.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,13,15 Preparation and processing conditions can be manipulated in bringing about thermomechanical changes in confined thin polymer films. 16–21 The practical difficulty in probing the properties of such thin films using traditional conventional mechanical testing techniques resulted in the development of nonconventional complementary techniques like dewetting, 22,23 wrinkling, 24,25 TUTTUT, 26 capillary leveling, 27 etc. The simplicity of the dewetting process and the ability to understand the polymer chain segment level properties make it a very useful technique.…”
Section: Introductionmentioning
confidence: 99%